Substâncias fenólicas e diterpênica de Casearia arborea (rich.) urb. (Salicaceae) e avaliação antimicrobiana do seu diterpeno - Ferreira, Maria Denise Leite (2016)
Casearia arborea (Rich.) Urb. (Salicaceae) also known as "peak wood", "yellow imbue" or "cinnamon", is found from Guatemala to Bolivia and Brazil. The phytochemical study of the species, using chromatographic techniques led to the isolation of flavonoid kaempferol 3-O-a-L-arabinofuranosídeo of leaves and flowers and 4 ', 5,7-trihydroxy-3', 5'-dimethoxy (Tricine) , and reisolation of Kolavalona (ent13-hydroxy-2-oxo-trans-3,14-diene-cleroda) of the stem. Both compounds were characterized by spectroscopic analysis using Nuclear Magnetic Resonance 1H and 13C one- and two-dimensional. The antimicrobial activity of Kolavelona substance was carried out in several strains, determining its minimum inhibitory concentration (MIC), the antibacterial activity of the compound was considered excellent front of the tested bacteria, and only active front of the yeast of the species Candida tropicalis